Amood Al-Sher In Arabic Literature The Elegy Of Abu Al-Ala Al-Ma'arri For His Mother - Al-Saedi, Saleh Salem (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The research describes the systematic development of Arab critical theory in Arab heritage. This research applies Al-Marzuqi's 'Amood al-Sher' theory to the elegy penned by Abu al-Ala Al-Ma'arri for his mother. The methodology follows the distribution of Al-Marzuqi's seven articles for the 'Amood al-Sher' and its application to Abu al-Ala Al-Ma'arri's elegy for his mother. This research also examines an ideology on the possibilities of creativity in ancient Arab criticism despite numerous contradictory viewpoints. In addition, it makes a concerted effort to reconsider the